Spontaneous Corneal Clearance after Descemet’s Stripping Without Endothelial Replacement - Shah, Rupa D. (2011)
PURPOSE: To report spontaneous corneal clearing with improved visual acuity and central endothelial cell repopulation after Descemet’s stripping without endothelial replacement. DESIGN: Interventional case report. METHODS: A 34 year-old female with bilateral decreased vision secondary to corneal edema from endothelial dysfunction underwent Descemet’s stripping endothelial keratoplasty (DSEK) in the right eye and Descemet’s stripping (DS) only in her contralateral eye. Histopathologic evaluation confirmed a dual diagnosis of Fuchs endothelial dystrophy (Fuchs) and posterior polymorphous membrane dystrophy (PPMD) from Descemet’s membrane specimens removed from each eye. Following primary graft failure with regraft in the right eye, the second posterior corneal lenticule detached, was removed and was not replaced. The cornea cleared and central endothelial cell repopulation was documented by confocal microscopy. Therefore, Descemet’s stripping without endothelial replacement was performed in the left eye. The left cornea also cleared with central endothelial cell repopulation. MAIN OUTCOME MEASURES: Postoperative visual acuity and central endothelial cell repopulation RESULTS: Endothelial migration after Descemet’s stripping alone in the second eye, with probably host endothelial cell repopulation in the right eye. CONCLUSIONS: Endothelial cell migration after Descemet’s stripping procedure without insertion of endothelial graft can occur, resulting in host endothelial cell repopulation with corneal clearing and improved visual acuity.